Interest and Science Process Skills in Science Education Based on Gender - Retni Sulistiyoning Budiarti; Dwi Agus Kurniawan; Rahmat Perdana; Sabila Eka Septi; Rahmi Rahmi (Universitas Pendidikan Ganesha, 2022)
The importance of students' interest in learning is learning skills, so research is carried out to assess students' interests and skills in depth based on grade level and gender in a school so that interests and skills can be known in depth based on the indicators tested. There has been no research that examines student interest and science process skills in detail based on grade level and generation in a school. So the autor make this study with purpose to analyze how the interest and science process skills between women and men compare in science subjects and to analyze how the relationship between students' interests and science process skills with science subjects. This study uses a quantitative method with a comparative type. Quantitative research is a field of inquiry that stands alone, is scientific in nature and aims to understand social reality. The instrument in this study used a questionnaire and an observation sheet, namely a student interest questionnaire and an observation sheet for science process skills. Based on the results of hypothesis testing, research testing and data analysis, the conclusion of this study is from the T-test there are differences in the interests of female students and male students in class VII A and VII B. From the results of the T test for students' science process skills there are differences in the interests of female students and male students in grades VII A and VII B. Based on the results of the correlation test between interests and science process skills of grade VII A students there is a relationship between interests and science process skills between female and male students as well as in class VII B. Students' interest and science process skills have a significant influence on curiosity, learning materials and teacher attitudes, student observation and communication.